2021
DOI: 10.3390/v13040597
|View full text |Cite
|
Sign up to set email alerts
|

The Portal Vertex of KSHV Promotes Docking of Capsids at the Nuclear Pores

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is a cancer-related herpesvirus. Like other herpesviruses, the KSHV icosahedral capsid includes a portal vertex, composed of 12 protein subunits encoded by open reading frame (ORF) 43, which enables packaging and release of the viral genome into the nucleus through the nuclear pore complex (NPC). Capsid vertex-specific component (CVSC) tegument proteins, which directly mediate docking at the NPCs, are organized on the capsid vertices and are enriched on the portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…Combined, our observations suggest that reduced levels of CVSC proteins on A-and B-capsids compared to that of C-capsids, result in lower capsid-NPC binding. Our findings are supported by recently published data for Kaposi's sarcoma-associated herpesvirus (KSHV) showing that KSHV capsids (with capsid structure homologous to HSV-1 capsids) dock at the NPCs even when portal-ring-forming protein ORF43 is deleted (ORF43-null KSHV capsids) [15]. Based on this result, authors suggest that capsid-NPC binding is mediated by CVSC complexes at non-portal penton vertices (this type of non-portal binding results in infection "dead-end" particles since DNA cannot be ejected) [15].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Combined, our observations suggest that reduced levels of CVSC proteins on A-and B-capsids compared to that of C-capsids, result in lower capsid-NPC binding. Our findings are supported by recently published data for Kaposi's sarcoma-associated herpesvirus (KSHV) showing that KSHV capsids (with capsid structure homologous to HSV-1 capsids) dock at the NPCs even when portal-ring-forming protein ORF43 is deleted (ORF43-null KSHV capsids) [15]. Based on this result, authors suggest that capsid-NPC binding is mediated by CVSC complexes at non-portal penton vertices (this type of non-portal binding results in infection "dead-end" particles since DNA cannot be ejected) [15].…”
Section: Resultssupporting
confidence: 87%
“…It has been observed that docking of HSV-1 at the NPC is mediated by the minor capsid protein UL25, which binds Nup214 situated on the cytoplasmic NPC surface [10,11], and by tether tegument protein UL36, which binds Nup358 localized on the cytoplasmic NPC filaments [9,14] (gene names are used to refer to their respective proteins). It was suggested that these interactions ensure alignment of the capsid portal with the NPC opening pore, facilitating DNA ejection into the nucleoplasm [15]. The HSV-1 capsid is comprised mainly of the major capsid protein VP5 (UL19), organized in 11 pentameric (penton forming vertices) and 150 hexameric (hexon) capsomer subunits [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using a pull-down assay combined with qPCR, we showed earlier that HSV-1 capsid–NPC binding in isolated reconstituted nuclei triggers the ejection of viral DNA and its internalization in the nucleus, driven by capsid DNA pressure of ∼18 atm ( 10 ). A benefit of the reconstituted virus–nucleus system is that it can be used to isolate the effect of the central step of viral infection—capsid docking at the nucleus and viral genome uncoating—on nucleus mechanics while avoiding interference from other processes occurring within the cell cytoplasm during viral replication ( 12 ). There are, on average, more than a thousand NPCs covering a significant area of the nucleus surface ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 9 ) of cell-free reconstituted nuclei incubated with HSV-1 capsids, which dock at the nuclear pore complexes (NPCs) and eject their DNA into the nucleus ( 10 , 11 ). This isolated nucleus system recapitulates capsid–nucleus binding and viral DNA ejection (without DNA replication) in vivo without interference from trafficking kinetics of capsids moving toward the nucleus ( 12 ) while allowing direct probing of nucleus mechanics with the AFM cantilever. Previously, nucleus mechanics was investigated with AFM studies in intact cells ( 13 ).…”
mentioning
confidence: 99%
“…One conserved function most likely involves capsid docking at the nucleus and genome delivery. KSHV capsids lacking a portal complex do not efficiently dock at the nucleus [102], likely because the portal vertex also lacks the CATC. CATC proteins may also have subfamilyspecific functions.…”
Section: Functional Roles Of Gammaherpesvirus Catc Proteinsmentioning
confidence: 99%